Les titres dans la conversation des arts en France De la fin des années 1890 aux années 1920 - Grau, D (2016)
The status of titles in both painting and literature changed dramatically during the 19th century, as their largely enonciative function evolved to become a form of metaphor, and even disjunction. The use of titles as tools for communication became increasingly evident, as they conveyed views on the overall positioning of art and literature. Painting and literature themselves were undergoing considerable changes, as the figures of the writer and the artist gained consistency and independence. This led to the "crise exquise" diagnosed by Mallarmé in "Crise de vers" (1896). This fin-de-siècle 'crisis' is the starting-point for the analysis undertaken in this thesis, which aims to examine, first, how artists and writers used titles to establish communication between their respective art-forms; then, how titles provided a privileged means of entry into the debates about the relation of painting and literature to the world at large. An exploration of late 19th- and early 20th-century painting and literature in Paris -- from post- Mallarmean Symbolism to the beginnings of Surrealism -- the thesis draws on two methodologies: title studies, as they have developed since the 1950s; and existing work on the dialogue between artists and writers. It is composed of six comparative case studies, tracing a genealogy from Paul Gauguin and Alfred Jarry to André Breton and Max Ernst, including discussions of Paul Cézanne and Emile Zola, André Gide and Henri Matisse, Guillaume Apollinaire and Pablo Picasso, Francis Picabia and Tristan Tzara. These comparisons reveal a polarity between two different lineages: one that emphasizes the specificity of each medium and engages with it within the framework of its boundaries, and does not seek to communicate with the world outside their work of art; and the other, which blurs the boundaries between different art-forms and simultaneously engages with the evolutions taking place in culture.